PELAKSANAAN PROGRAM CORPORATE FARMING PADA KELOMPOK TANI BAROKAH, KECAMATAN JETIS, KABUPATEN BANTUL - Perdana, Putri (Agros Journal of Agriculture Science, 2024)
Corporate Farming (CF) conducted in Trimulyo Hamlet, Jetis District, Bantul Regency with the Barokah Farmers Group is a pilot project from Bank Indonesia as one of the innovations in the field of agricultural institutions to realize more effective and efficient agriculture through rice field consolidation. The implementation of this program is carried out with a three-year contract. The purpose of this study is to describe the implementation of the CF program carried out by the Barokah Farmers Group. This study was conducted using purposive sampling by censusing 51 owner-cultivator farmers who are members of the Barokah Farmers Group and have implemented the CF program. The statements used in this study were tested using validity and reliability tests. The results of the study showed that the implementation of the CF program was 78.43% by applicable principles.